Reassessing Values and Implementation in Islamic Education: A Critical Axiological Review - Safitri, Diana; Rijal, Syamsul; Yunus, Firdaus M. (Lembaga Yasin AlSys, 2024)
The application of values ​​is the basis of Islamic education because it aims to teach a person's attitude towards the Creator and nature contained in Islamic teachings by teaching commendable behavior based on the Qur'an and Al-Hadith. The researcher used library research by collecting data from various search engine references. The researcher also carried out several stages in data analysis techniques. The results of the study indicate that the components of the objectives, materials, methods, and roles of teachers of Islamic religious education must help each other to achieve the goals of applying values. The principles taught in Islamic religious education include the values ​​of faith, morals, and worship. The values ​​studied in this work are the values ​​of piety and knowledge obtained by students from the learning process. By applying these values ​​in their education, students will find it easy to understand and use. It is in their daily activities so that they can more easily avoid the negative impacts of the development of the times. The benefit of this study is finding a form of implementation of the values ​​of Islamic teachings, namely piety and scientific material, in daily behavior. Implementation in Islamic education influences the behavior of devotion to Allah through acts of worship and behavior towards nature.